Dioxin risk assessment: mechanisms of action and possible toxicity in human health - Sany, S.B.T.; Hashim, R.; Salleh, A.; Rezayi, M.; Karlen, D.J.; Razavizadeh, B.B.M.; Abouzari-lotf, E. (2015)
Dioxin-like compounds (DLCs) have been classified by the World Health Organization (WHO) as one of the most persistent toxic chemical substances in the environment, and they are associated with several occupational activities and industrial accidents around the world. Since the end of the 1970s, these toxic chemicals have been banned because of their human toxicity potential, long half-life, wide dispersion, and they bioaccumulate in the food web. This review serves as a primer for environmental health professionals to provide guidance on short-term risk assessment of dioxin and to identify key findings for health and exposure assessment based on policies of different agencies. It also presents possible health effects of dioxins, mechanisms of action, toxic equivalency factors (TEFs), and dose-response characterization. Key studies related to toxicity values of dioxin-like compounds and their possible human health risk were identified through PubMed and supplemented with relevant studies characterized by reviewing the reference lists in the review articles and primary literature. Existing data decreases the scope of analyses and models in relevant studies to a manageable size by focusing on the set of important studies related to the perspective of developing toxicity values of DLCs.